Conversion of Aldehydes to Acylals Using Acetic Anhydride in Presence of Catalytic Amount of Fe(NO3)3·9H2O Under Solvent-Free Conditions at Room Temperature - Khazaei, Ardeshir; Amini Manesh, Abbas; Rostami, Amin; Ali Alavi-Nik, Heidar; Toodeh Roosta, Zahra (Asian Journal of Chemistry, 2010)
Fe(NO3)3·9H2O efficiently catalyzed the conversion of aromatic and aliphatic aldehydes to 1,1- diacetates under solvent-free conditions at room temperature. This study reports the use of Fe(NO3)3·9H2O which is highly efficient, chemoselective, eco-friendly non-toxic and cost effective catalyst for use in the conversion of aldehydes to acylals. Short reaction times and good yields are another advantages of this method. 4-Dimethylaminobenzaldehyde and ketones did not react under the same conditions.